Duelo patológico y su incidencia en la vida diaria de una adulta mayor de 70 años de la ciudad de Babahoyo - Tamayo León, Jisleine Dennisse (2023)
This case study focuses on the impact of pathological grief on the daily life of an elderly woman over 70 years old in Babahoyo. The loss of a loved one at an advanced age can be particularly traumatic and can trigger a series of emotional and psychological problems. This study seeks to understand the different manifestations of grief pathology and its relationship with depression, anxiety, and other physical and mental health problems. To do so, the cognitive-behavioral therapy model has been applied, using tools such as interview, observation, psychometric batteries, and specific intervention techniques. The results obtained indicate that the patient has experienced a series of symptoms that have affected her ability to perform daily activities, including personal care and participation in social activities.